Selective hydrogenation of aromatics in coal-derived liquids over novel NiW and NiMo carbide catalysts. (15th May 2019) - Zhang, Haiyong; Chen, Genwei; Bai, Lei; Chang, Ning; Wang, Yonggang
Abstract: Novel bimetallic NiW/Al2 O3 and NiMo/Al2 O3 carbide catalysts were prepared by temperature-programmed reaction with CH4 -H2 mixture. The catalysts were characterized by N2 adsorption, XRD, TPR and their performance for selective hydrogenation of aromatics in coal derived liquids were compared with their sulfide counterparts. Direct coal liquefaction oil (DCLO) fraction in 180∼290 °C and aromatic component separated from low temperature coal tar (LTCT) fraction in 210∼290 °C were selected as feedstock and hydrogenated on a fixed bed micro-reactor. The results of elemental analysis, simulated distillation and GC-MS show that the hydrodearomatization (HDA) activity was: NiMo-C > NiW-C > NiW-S > NiMo-S. The HDA, Hydrodenitrogenation (HDN) and hydrodesulfurization (HDS) for DCLO hydrogenation over NiMo-C is 91%, 29.54% and 75.23%, respectively. The hydroaromatics and cycloalkanes in hydrogenated LTCT and DCLO products were 67.1% and 74.8%, respectively. Thus, NiMo carbide is a promising catalyst for selective hydrogenation of CDLs to obtain high performance jet fuel blend which is rich in hydroaromatics and cycloalkanes.